Bodźce ikoniczne w zintegrowanym nauczaniu mówienia i pisania - Morcinek, Barbara (Neofilolog, 2010)
Efficient teaching of speaking and writing in a foreign language is always a challenge. In particular, the development of productive skills requires the employment of a variety of methods designed to provide necessary encouragement. Teaching Polish in a country as distant from Poland as Japan seems to be even more demanding than might be the case with more popular languages, such as English, because students have very limited opportunities to use Polish in their daily lives. My solution involves the use of pictures, employed in the course of the class as cues stimulating students imagination and thus generating a context conducive to real communication.